Search for neutrinoless tau decays involving pi(0) or eta mesons - Bonvicini, G; Cinabro, D; Greene, R; Perera, L; Zhou, G; Barish, B; Chadha, M; Chan, S; Eigen, G; Miller, J; OGrady, C; Schmidtler, M; et al. (1997)
We have searched for lepton flavor violating decays of the τ lepton with one or two KS 0 mesons in the final state. The data used in the search were collected with the CLEO II and II.V detectors at the Cornell Electron Storage Ring (CESR) and correspond to an integrated luminosity of 13.9 fb-1 at the Y (4S) resonance. No evidence for signals were found; therefore, we have set 90% confidence level (C.L.) upper limits on the branching fractions Β(τ- → e- K S 0)<9.1×10-7, Β(τ- →μ- KS 0)<9.5×10-7, Β(τ- → e-KS 0K S 0) <2.2× 10-6, and Β(τ- → μ- KS 0K S 0)<3.4×10-6. These represent significantly improved upper limits on the two-body decays and first upper limits on the three-body decays. © 2002 The American Physical Society.